THE EFFECT OF LIQUIDITY ON PROFITABILITY (CASE STUDY ON A FOOD AND BEVERAGE COMPANY LISTED ON THE STOCK EXCHANGE INDONESIA PERIOD 2015-2017) - Ayu Luckyta Putri; Anne Lasminingrat (Jurnal Visi Manajemen, 2020)
This study aims to examine how profitability for food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2015 and 2017 is affected by liquidity.A case study methodology is used in this research's quantitative method, which involves gathering data through library studies and documentation. In this study, the time series analysis and the population cross section were combined using the data panel method (Eviews 8.0). The population in this study consisted of 10 out of the 18 food and beverage companies that were listed on the Indonesia Stock Exchange (IDX). The samples were chosen using the purposive sampling method.The outcomes of the data analysis served as the foundation for the study's findings. It was possible to get the conclusion that the CR variable significantly influenced the ROA variables. The chi square Cross Section probabilities exceeded the levels of significance.The results of the current ratio have an impact on the return on assets, which is likely to be above a substantial level.Future study should incorporate the ideas offered, as well as methodologies that can be used to measure more variables. Adding samples can further lengthen the research period.